Comparative Evaluation of Anti-HER2 Affibody Molecules Labeled with 64Cu Using NOTA and NODAGA. (28th February 2017) - Tolmachev, Vladimir; Yim, Cheng-Bin; Rajander, Johan; Perols, Anna; Karlström, Amelie Eriksson; Haaparanta-Solin, Merja; Grönroos, Tove J.; Solin, Olof; Orlova, Anna
Abstract : Imaging using affibody molecules enables discrimination between breast cancer metastases with high and low expression of HER2, making appropriate therapy selection possible. This study aimed to evaluate if the longer half-life of 64 Cu (T 1 / 2 = 12.7 h) would make 64 Cu a superior nuclide compared to 68 Ga for PET imaging of HER2 expression using affibody molecules. The synthetic ZHER2:S1 affibody molecule was conjugated with the chelators NOTA or NODAGA and labeled with 64 Cu. The tumor-targeting properties of 64 Cu-NOTA-ZHER2:S1 and 64 Cu-NODAGA-ZHER2:S1 were evaluated and compared with the targeting properties of 68 Ga-NODAGA-ZHER2:S1 in mice. Both 64 Cu-NOTA-ZHER2:S1 and 64 Cu-NODAGA-ZHER2:S1 demonstrated specific targeting of HER2-expressing xenografts. At 2 h after injection of 64 Cu-NOTA-ZHER2:S1, 64 Cu-NODAGA-ZHER2:S1, and 68 Ga-NODAGA-ZHER2:S1, tumor uptakes did not differ significantly. Renal uptake of 64 Cu-labeled conjugates was dramatically reduced at 6 and 24 h after injection. Notably, radioactivity uptake concomitantly increased in blood, lung, liver, spleen, and intestines, which resulted in decreased tumor-to-organ ratios compared to 2 h postinjection. Organ uptake was lower for 64 Cu-NODAGA-ZHER2:S1. The most probable explanation for this biodistribution pattern was the release and redistribution of renal radiometabolites. In conclusion, monoamide derivatives of NOTA and NODAGA may be suboptimal chelators for radiocopper labeling of anti-HER2 affibody molecules and, possibly, other scaffold proteins with high renal uptake.